2017
DOI: 10.18203/2349-3291.ijcp20174154
|View full text |Cite
|
Sign up to set email alerts
|

Adherence to antiretroviral therapy and factors affecting adherence among paediatric HIV patients

Abstract: Background: Adherence to antiretroviral therapy (ART) is the strongest indicator of successful treatment of Human Immunodeficiency Virus (HIV) among children. The main aim of the present study was to know the prevalence of adherence at our centre and various factors affecting the adherence in children.Methods: It was an observational study done in children less than 15 years of age, affected with HIV.  78 children attending Paediatric Centre of Excellence (PCOE) for HIV L.T.M.G. Hospital, Sion, Mumbai were inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
1
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 19 publications
2
1
1
Order By: Relevance
“…28 Again, our finding is also similar to the finding of a study conducted in India that came up with, children whose caregivers had good knowledge about ART treatment were 14.7 times more adherent. 32 A similarly study conducted in north Ethiopia, justified our finding (AOR = 2.72). 33 Our finding is again in line with the study finding conducted at University of Gondar Hospital and Gondar Poly Clinic, which showed that children of knowledgeable caregivers had 4.7 times more adherent to ART than their counterparts (AOR = 4.7).…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…28 Again, our finding is also similar to the finding of a study conducted in India that came up with, children whose caregivers had good knowledge about ART treatment were 14.7 times more adherent. 32 A similarly study conducted in north Ethiopia, justified our finding (AOR = 2.72). 33 Our finding is again in line with the study finding conducted at University of Gondar Hospital and Gondar Poly Clinic, which showed that children of knowledgeable caregivers had 4.7 times more adherent to ART than their counterparts (AOR = 4.7).…”
Section: Discussionsupporting
confidence: 85%
“… 31 However, the finding of the current study was higher than the finding of study conducted in India, which revealed an overall adherence of 82.1%. 32 This difference might be due to the study design (cross-sectional vs. cohort). It was also higher than that in a study in Uganda which reported an overall adherence status of 79.1%), 33 North Ethiopia, provided an adherence status of 78.6%, 22 and central Ethiopia showed an adherence rate of 74%.…”
Section: Discussionmentioning
confidence: 99%
“…Hospital and Gondar Poly Clinic, 90.4% (23), Addis Ababa 86.9% (24). But the nding of current study was higher than the nding of the study conducted by Govind M. et al in India, that revealed an overall adherence of 82.1% (25). This difference might be due to study design (cross sectional vs cohort).…”
Section: Discussioncontrasting
confidence: 67%
“…Our nding is similar to the study nding conducted in Hiwot Fana and Dil-Chora hospital that revealed caregivers of children with good knowledge about the disease were 7.3 times [AOR = 7.3] adherent than their counter parts(21). Again our nding is also similar to the nding of study conducted in India that came up with, children whose caregivers have good knowledge about ART treatment were 14.7 times more adherent(25). Similarly study conducted in south Wollo zone was justify Current study also provided that children residing in urban area were 3.2 times more adherent to ART than those who residing in rural.…”
supporting
confidence: 86%